2011
DOI: 10.1002/cne.22563
|View full text |Cite
|
Sign up to set email alerts
|

Differential structural plasticity of corticostriatal and thalamostriatal axo‐spinous synapses in MPTP‐treated parkinsonian monkeys

Abstract: Striatal spine loss is a key pathological feature of Parkinson's disease (PD). Knowing that striatal glutamatergic afferents target dendritic spines, these data appear difficult to reconcile with evidence for an increased expression of the vesicular glutamate transporter 1 (vGluT1) in the striatum of PD patients and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated monkeys, as well as in some electrophysiological studies showing overactivity of the corticostriatal glutamatergic system in models of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 80 publications
(150 reference statements)
11
87
2
Order By: Relevance
“…This suggests that the observed coherence changes are associated with, but are not causal of, parkinsonism, and that they may not be primarily dopaminergic in origin. It is possible that these coherence changes result instead from other changes in the basal ganglia, thalamus, or cortex that are known to accompany parkinsonism in human PD and in MPTP-treated primates, such as changes in striatal spine density, loss of the thalamostriatal system, or changes in non-dopaminergic transmitter systems, such as the noradrenergic or serotonergic systems (Villalba and Smith, 2011; Villalba et al, 2009). Such changes would not be expected to be reversible by acute stimulation of dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the observed coherence changes are associated with, but are not causal of, parkinsonism, and that they may not be primarily dopaminergic in origin. It is possible that these coherence changes result instead from other changes in the basal ganglia, thalamus, or cortex that are known to accompany parkinsonism in human PD and in MPTP-treated primates, such as changes in striatal spine density, loss of the thalamostriatal system, or changes in non-dopaminergic transmitter systems, such as the noradrenergic or serotonergic systems (Villalba and Smith, 2011; Villalba et al, 2009). Such changes would not be expected to be reversible by acute stimulation of dopamine receptors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also provide a proof-of-principle demonstration that in patients suffering from decreased PSD-95 levels, as occurs in ASD, restoration Electron microscopic analysis. As described previously (65), PSD measurements were performed with ImageJ software (NIH) by an observer blinded to the genotype of the animals. Results are expressed as the mean ± SEM.…”
Section: Methodsmentioning
confidence: 99%
“…These include a growing list of chronic morphological changes in the basal ganglia, affecting glutamatergic and GABAergic transmission in these structures. For instance, plasticity at glutamatergic synapses has been demonstrated in animal models of parkinsonism and in patients with PD, affecting the corticostriatal, thalamostriatal, and corticosubthalamic pathways [166][167][168][169][170][171][172][173]. Recent studies have suggested additional plasticity of the GABAergic collaterals within the GPe, as well as the pallidosubthalamic projection, the latter perhaps related to heterosynaptic homeostatic modulations, driven by N-methyl-D-aspartate receptor activation at corticosubthalamic synapses [157,158,174].…”
Section: Pathophysiology Of Parkinsonism and Dystoniamentioning
confidence: 99%